Efficacy and safety of efpeglenatide in key patient subgroups from the BALANCE randomized trial, stratified by pre-diabetes status, BMI, and age at baseline. Issue 1 (18th January 2022) - Pratley, Richard E; Jacob, Stephan; Baek, Seungjae; Trautmann, Michael E; Hompesch, Marcus; Han, OakPil; Stewart, John; Sorli, Christopher H; Shaunik, Alka; Yoon, Kun-Ho
Abstract : Introduction: Efpeglenatide is a long-acting glucagon-like peptide-1 receptor agonist being developed to improve glycemic control in type 2 diabetes (T2D). In the BALANCE 205 study (NCT02075281 ), efpeglenatide significantly reduced body weight versus placebo in patients with obesity, or overweight with comorbidities, and without T2D. These subanalyses explore the efficacy and safety of efpeglenatide in subgroups of patients with pre-diabetes and stratified by body mass index (BMI) or age from the BALANCE study. Research design and methods: The 20-week BALANCE study randomized patients with BMI ≥30 kg/m 2 or ≥27 kg/m 2 with comorbidities, and without diabetes, to efpeglenatide 4 mg or 6 mg once weekly, 6 mg or 8 mg once every 2 weeks, or placebo. For these subanalyses, patients were stratified by pre-diabetes status (glycated hemoglobin (HbA1c ) 5.7%−6.4% (39–46 mmol/mol) or fasting plasma glucose (FPG) 100–125 mg/dL) and by BMI or age < or ≥ median values (34.9 kg/m 2 and 44 years, respectively) at baseline. Results: In patients with pre-diabetes at baseline, all efpeglenatide doses led to greater proportions of patients reverting to normoglycemia (40.6%–64.3%) versus placebo (10.0%), and greater reductions in HbA1c (0.30%–0.38%), FPG (7.7–14.1 mg/dL), and weight (5.6–7.3 kg) versus placebo (nominal p<0.05 for all). In patients with BMI or age < or ≥ median, greater reductions in weight were observed with all efpeglenatide doses versus placebo (nominal p<0.01 for all). The most common adverse events in patients receiving efpeglenatide across patient subgroups were gastrointestinal adverse events. Conclusions: These results are consistent with the overall BALANCE population and suggest beneficial effects of efpeglenatide on glycemic control and body weight regardless of pre-diabetes status, age, or BMI at baseline. The effects of efpeglenatide on glycemic control in patients with pre-diabetes suggest it might help reduce the likelihood of at-risk patients developing diabetes.